Konsep dan aplikasi konseling olahraga bagi atlet; peluang dan tantangan - Tjung Hauw Sin (Indonesian Institute for Counseling, Education and Therapy (IICET), 2019)
The development of the world is now complex, problems are diverse, including in sports settings. The problem of athletes is more complex, not a few athletes who do not compete because of low self-management, unstable emotional control and even motivation and performance that are not optimal. Not to mention the condition of the relationship between athletes and athletes, athletes with coaches and even family problems that are Carrie away and affect psychological conditions during sparring in the field. The condition requires the existence of a special psychological companion for athletes, this condition makes the background of the need for sports counseling, a sports counselor can accompany the need for special personnel skilled and mastering the psychological concepts of athletes. This has become a new alternative for counselors in performing. Script will present the background of the need for sports counseling services, athlete’s problems, direction of sports counseling services and opportunities and challenges.